Prioritisation of genetic innovations targeted to CWANA - product profile and demand creation stakeholder consultation meeting, Uzbekistan - Sanchez-Garcia, Miguel; Bishaw, Zewdie (International Center for Agricultural Research in the Dry Areas, 2023)
A series of hybrid country-focused meetings took place between NARES, national and regional stakeholders, CGIAR breeders and F2R-CWANA WP2 researchers to promote the fast-track release of the most suitable Genetic Innovations for the CWANA region. Participants were familiarized with OneCGIAR strategies to disseminate Genetic Innovations and were asked to prioritize, firstly, the crops and crop- Target Product Profiles (TPPs) available in the OneCGIAR portfolio that were considered most important for the countries. Prioritization was based, among other considerations, on their socioeconomic importance for the country and the current availability of suitable varieties targeting the TPPs selected. Secondly, newly released but underutilized varieties that best fit the selected TPPs were also prioritized. The prioritized county and crop-level target product profiles and newly released varieties will be the basis of subsequent activities related to developing and releasing genetic innovations within CWANA under WP2. This record is for the stakeholder engagement meeting in Uzbekistan.